Southern Ocean sea ice, icebergs, and meteorological data from maritime sources for the period 1929 to 1940 - Divine, Dmitry V.; Divina, Svetlana; Bjørge, Ole Edvard; Isaksson, Elisabeth; Jølle, Harald Dag; Stokkeland, Ivar; Vasquez Guzman, Mariela; Wilkinson, Sally; Wilkinson, Clive (Geoscience Data Journal, 2024)
Maritime historical documentary sources of weather and state of sea surface including sea ice can aid in filling a known climate knowledge gap for the Southern Ocean and Antarctica for the first half of the 20th century. This study presents a data set of marine climate, sea ice and icebergs recovered from a collection of logbooks from mainly Norwegian whaling factory ships that operated in the Southern Ocean during 1929-1940. The data set comprises some 8000 weather and 4000 sea ice/open sea records from austral summers of the study period. This paper further discusses the structure and content of most common Norwegian maritime documentary sources of the period along with the practices of logging information relevant for the study, such as time keeping, positioning and making weather observations. An emphasis was made on recovery of notes on sea ice and icebergs and their interpretation in terms of WMO categories of sea ice concentration. Data, including ship-related metadata from all individual documents are homogenized and structured to a common machine-readable format that simplifies its ingestion into relevant climate data depositories.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; hvalfangst; isberg; klima; meteorologi; sjøis; skipsloggbøker

Antarctic petrels ‘on the ice rocks’: wintering strategy of an Antarctic seabird - Delord, Karine; Kato, Akiko; Tarroux, Arnaud; Orgeret, Florian; Cotté, Cedric; Ropert-Coudert, Yan; Cherel, Yves; Descamps, Sébastien (Royal Society Open Science, 2020)
There is a paucity of information on the foraging ecology, especially individual use of sea-ice features and icebergs, over the non-breeding season in many seabird species. Using geolocators and stable isotopes, we defined the movements, distribution and diet of adult Antarctic petrels Thalassoica antarctica from the largest known breeding colony, the inland Svarthamaren, Antarctica. More specifically, we examined how sea-ice concentration and free-drifting icebergs affect the distribution of Antarctic petrels. After breeding, birds moved north to the marginal ice zone (MIZ) in the Weddell sector of the Southern Ocean, following its northward extension during freeze-up in April, and they wintered there in April–August. There, the birds stayed predominantly out of the water (60–80% of the time) suggesting they use icebergs as platforms to stand on and/or to rest. Feather δ15N values encompassed one full trophic level, indicating that birds fed on various proportions of crustaceans and fish/squid, most likely Antarctic krill Euphausia superba and the myctophid fish Electrona antarctica and/or the squid Psychroteuthis glacialis. Birds showed strong affinity for the open waters of the northern boundary of the MIZ, an important iceberg transit area, which offers roosting opportunities and rich prey fields. The strong association of Antarctic petrels with sea-ice cycle and icebergs suggests the species can serve, year-round, as a sentinel of environmental changes for this remote region.
Keywords: Sørishavet; Weddellhavet; biologi; geolokalisering; havis; isberg; isfjell; klimaendringer; miljøendringer; ornitologi; petreller; sjøfugler; sjøis; økologi